2023
DOI: 10.1021/acsnano.2c12168
|View full text |Cite
|
Sign up to set email alerts
|

A General and Scalable Approach to Sulfur-Doped Mono-/Bi-/Trimetallic Nanoparticles Confined in Mesoporous Carbon

Abstract: Metal nanoparticles confined in porous carbon materials have been widely used in various heterogeneous catalytic processes due to their enhanced activity and stability. However, fabrication of such catalysts in a facile and scalable way remains challenging. Herein, we report a general and scalable thiol-assisted strategy to synthesize sulfur-doped mono-/bi-/trimetallic nanoparticles confined in mesoporous carbon (S-M@MC, M = Pt, Pd, Rh, Co, Zn, etc.), involving only two synthetic steps, i.e., a hydrothermal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…1f), which is in favor of the transport of electrolytes and liberation of gas to enhance the electrocatalytic activity. 36,37 The corresponding elemental mapping of 3D-NPOC showcases that the C, N, O, and P elements are evenly distributed in the whole framework of 3D-NPOC (Fig. 1g), well consistent with the XPS spectrogram results, which also indicates the successful preparation of the N, P, O co-doped carbon material.…”
Section: Resultssupporting
confidence: 78%
“…1f), which is in favor of the transport of electrolytes and liberation of gas to enhance the electrocatalytic activity. 36,37 The corresponding elemental mapping of 3D-NPOC showcases that the C, N, O, and P elements are evenly distributed in the whole framework of 3D-NPOC (Fig. 1g), well consistent with the XPS spectrogram results, which also indicates the successful preparation of the N, P, O co-doped carbon material.…”
Section: Resultssupporting
confidence: 78%
“…According to classical electromagnetic theory, the reflection of electromagnetic waves at the interface between air and a material depends on the difference in wave impedance, which in turn is affected by the electrical conductivity of the material. [54][55][56] Their superior electrical conductivity caused a higher R of all GFs. This phenomenon further demonstrated that the electromagnetic shielding of GF was primarily accomplished through reflection.…”
Section: Electrical Conductivity and Emi Se Of Gfsmentioning
confidence: 99%
“…The long-range oriented conductive network induces local microcurrent which brings about rapid attenuation of electromagnetic waves in multiple resistance networks. 52,56,58 In general, the absorption loss is related to the electromagnetic wave energy converted from the generated current and polarization relaxation. The existence of defects and folds in the GFs implies the presence of amorphous structures that serve as scattering sites and polarization centers to supply polarization loss.…”
Section: Electrical Conductivity and Emi Se Of Gfsmentioning
confidence: 99%
“…With the rapid development of deformable and wearable electronic devices, as well as an increasingly complex electromagnetic environment, high requirements have been proposed for electromagnetic interference (EMI) shielding materials. [1][2][3] To this end, high-performance, easy-manufacturing, low-cost, flexible, and intelligent EMI shielding materials are required to satisfy the current demands. [4][5][6] Of particular interest are intelligent responsive EMI shielding materials, which exhibit the capacity to dynamically acclimate to evolving scenarios, rendering them exceptionally well-suited for the forthcoming demands in both civilian and military domains.…”
Section: Introductionmentioning
confidence: 99%